PROGRAM KEMITRAAN MASYARAKAT (PKM) KLUSTER 2 PETERNAK AYAM RAS PETELUR SKALA USAHA MIKRO DAN USAHA KECIL DI KOTA TOMOHON TENTANG PENERAPAN BIOSEKURITI PADA USAHA PETERNAKAN UNGGAS: - - Tangkere, Evacuree S.; Podung, Albert J.; Tangkere, Imelda A.; Sompie, Florencia N.; Telleng, Malcky M. (PT. Jurnal Center Indonesia Publisher, 2026)
ABSTRACT The objective of community partnership program cluster 2 (CPP-C2) is to provide micro and small-scale layer chicken farmers in Tomohon city with business management procedures based on “biosecurity”. Problems faced by partners, both farm owners and farm workers: 1) lack of knowledge and understanding of the concept and application of biosecurity 2) lack of sanitation application, which increases the risk of diseases emerging and spreading 3) not yet aware that the use of open house system, unfenced farms and no procedures for entering the farm area, are not in accordance with the principles of biosecurity system. The activity was carried out in stages: survey, socialization on the concept and implementation of the 3-zone biosecurity system, provision of disinfectants and examples of regulation for laying hen farming as well as evaluation. The evaluation results show that during the extension activity, out of 8 participants only 2 were actively asking questions, and it turned out they were the farm owners, while the farm workers were passive. It was found after the outreach activity, that the farm owners or farm workers who were partners had not been implemented the 3-zone biosecurity system, therefore outreach activities regarding biosecurity on poultry farm still need to be provided again to them, so that the concept and application of biosecurity will be truly understood and they would be willing to do so. However, at least 2 farms have prepared signboards with rules for entering the farm area. The occurrence of outbreaks and pandemics should be a lesson-learned that biosecurity measures are highly relevant to the saying “it is better to prevent than cure”. If, chicken remain healthy, they produce high-quality and safe products, and so, farmers can minimize health costs and maximize profits, even enabling farms owner to expand their businesses scale. In conclusion, this activity has not been given a significant impact on partner’s farm management because all partners have not been implemented the 3-zone biosecurity system, and it would be better if, all farm owners as decision makers to participate in this kind of activity, as well as the need for synergy between relevant agencies in the livestock sector in Tomohon city and academics with poultry farming business practitioners in an effort to maintain livestock health, poultry communities and maintain food security.